Early Life Trauma and Attachment: Immediate and Enduring Effects on Neurobehavioral and Stress Axis Development - Rincón-Cortés, Millie; Sullivan, Regina M. (Frontiers in Endocrinology, 2014)
Over half a century of converging clinical and animal research indicates that early life experiences induce enduring neuroplasticity of the HPA-axis and the developing brain. This experience-induced neuroplasticity is due to alterations in the frequency and intensity of stimulation of pups’ sensory systems (i.e. olfactory, somatosensory, gustatory) embedded in mother-infant interactions. This stimulation provides “hidden regulators” of pups’ behavioral, physiological and neural responses that have both immediate and enduring consequences, including those involving the stress response. While variation in stimulation can produce individual differences and adaptive behaviors, pathological early life experiences can induce maladaptive behaviors, initiate a pathway to pathology and increase risk for later life psychopathologies, such as mood and affective disorders, suggesting that infant attachment relationships program later life neurobehavioral function. Recent evidence suggests that the effects of maternal presence or absence during this sensory stimulation provide a major modulatory role in neural and endocrine system responses, which have minimal impact on pups’ immediate neurobehavior but a robust impact on neurobehavioral development. This concept is reviewed here using two complementary rodent models of infant trauma within attachment: infant paired odor-shock conditioning (mimicking maternal odor attachment learning) and rearing with an abusive mother, that converge in producing a similar behavioral phenotype in later life including depressive-like behavior as well as disrupted HPA-axis and amygdala function. The importance of maternal social presence on pups’ immediate and enduring brain and behavior suggests unique processing of sensory stimuli in early life that could provide insight into the development of novel strategies for prevention and therapeutic interventions for trauma experienced with the abusive caregiver.